Peran Komunikasi Qur’anic terhadap Keharmonisan Keluarga Muslim Menurut Persepsi Ibu Rumah Tangga di RW 05 Kelurahan Pisangan Timur, Jakarta - Christiana Reali; Nirwan Syafrin (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Every husband and wife wants a harmonious, happy, and prosperous atmosphere in their family. As the most important organization in the community group to be responsible for the occurrence of social welfare and human sustainability. A quality and harmonious family is a family in which there is tranquility, love, peace, compassion, and the ability to work together. Qur'anic communication is one way to build family harmony as stated in the Qur'an. Without this it is difficult to build a harmonious family because of misunderstandings and conflicts. This journal examines how the role of qur'anic communication on family harmony according to housewives in RW 05 Pisangan Timur Jakarta using qualitative methods by conducting interviews and field observations. The result is that there is a role of qur'anic communication on family harmony which can be proven by the data obtained. Mother applies some qur'anic communication values ​​such as qawlan sadida, qawlan baligha and qawlan maysura and has an impact on increasing family harmony. Therefore, this journal tries to contribute ideas to inspire housewives to apply the value of qur'anic communication to increase harmony in the family. Keywords: Qur'anic Communication, Family, Harmonious, Housewife